Analisis Pelaksanaan Pelayanan Bisnis terhadap Peningkatan Kualitas Layanan pada Direktorat Bisnis dan Komersialisasi - Ariel Alpiansah; Andrian Noviardy (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This study aims to analyze the implementation of business services on improving service quality at the Directorate of Business and Commercialization of Bina Darma University. The research employed a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results showed that the implementation of business services has been carried out in accordance with established procedures, supported by information technology and competent human resources. The service quality provided is considered good based on SERVQUAL dimensions, including tangibles, reliability, responsiveness, assurance, and empathy. The main supporting factors include employee competence, technology utilization, work coordination, and adequate facilities and infrastructure. Constraints encountered include cross-unit coordination, increased workload, and technical disruptions in internet networks. Improvement efforts are conducted through periodic evaluations, employee competency enhancement, and strengthening service systems. This study concludes that the implementation of business services plays an important role in improving service quality, thus the better the implementation of business services, the better the quality of services produced.